Edukasi Pentingnya Pemenuhan Gizi Seimbang pada Balita di Dusun Sorogem, Pojoksari, Ambarawa - Wahyuningsih, Dyah; Heni Hirawati Pranoto; Afidah Wahyuni; Hesti Hanafi Agustin; Mawar Kusuma Ningrum; Mulia Rahmi Sapitri; Rudy Chawari Setia Ningsih (Universitas Ngudi Waluyo, 2023)
Stunting is a nutritional problem in children that needs attention. The results of the assessment of nutritional status in toddlers in Sorogem Hamlet, Pojoksari Village, there are 9 toddlers who are at risk of stunting. Insufficient nutritional intake in toddlers can be caused by a lack of maternal knowledge about balanced feeding. This encouraged us to conduct balanced nutrition counseling for mothers of toddlers directly at Sorogem Village Hall on May 11, 2023, which was attended by 25 mothers of toddlers. This activity consists of several stages, starting with filling out the Pre-test questionnaire, followed by health education about balanced nutrition in toddlers, questions and answers and filling out the post test and ending with the distribution of prizes for active mothers of toddlers. The results of the pre-test showed that most mothers' knowledge was in the sufficient category 19 mothers (76%). The post test results showed that most mothers of toddlers were in the good category 13 mothers (52%), indicating that there was an increase in knowledge from the pre-test results which were previously in the moderate category, to good after being given education. After counseling activities on nutrition in toddlers, there was an increase in knowledge from mothers. Abstrak Stunting merupakan permasalahan gizi pada anak yang perlu mendapat perhatian. Hasil pengkajian status gizi pada balita di Dusun Sorogem Desa Pojoksari, terdapat 9 balita yang beresiko stunting. Asupan gizi yang kurang pada balita dapat disebabkan kurangnya pengetahuan ibu tentang pemberian makanan seimbang. Hal tersebut mendorong kami untuk melakukan penyuluhan gizi seimbang pada Ibu Balita langsung di Balai Desa Sorogem pada tanggal 11 Mei 2023, yang diikuti oleh 25 Ibu Balita. Kegiatan ini terdiri dari beberapa tahapan, diawali dengan pengisian kuesioner Pre-test, dilanjutkan dengan pendidikan kesehatan tentang gizi seimbang pada balita, tanya jawab dan pengisian post test dan diakhiri dengan pembagian hadiah untuk ibu balita yang aktif. Hasil pre test menunjukkan sebagian besar pengetahuan Ibu dalam kategori cukup 19 Ibu (76%). Hasil post test menunjukkan sebagian besar ibu balita dalam kategori baik 13 ibu (52%), menunjukkan bahwa terjadi peningkatan pengetahuan dari hasil pre test yang sebelumnya kategori cukup, menjadi baik setelah diberikan edukasi. Setelah dilakukan kegiatan penyuluhan tentang gizi pada balita, terjadi peningkatan pengetahuan dari para ibu.